Spotting technique faults - below & above the water - Pease, D. (coachesinfo.com, 1999)
Due to the highly technical nature of swimming, the technique that a swimmer uses is vital to maximising their performance. The difficulty with analysing swimming technique is that it takes place in two mediums, air and water. Due to the effects of refraction as light passes through water, it is difficult to identify technique flaws by looking from the pool side alone. In order to get around this problem coaches and researchers have turned to examining swimmers both, visually through underwater windows or with underwater video/film cameras, which provide non-distorted views of the athletes' technique, and indirectly with other types of equipment. This presentation discusses most of the current methods used for technique analysis, both above and below the water surface and outlines the advantages and disadvantages of the various techniques. The methods are: - Visual Observation Methods - Stroke Rate / Stroke Length - Underwater Window Observation - Videotaping - Flume Observation & Video Analysis - Indirect Methods of Technique Analysis - Tethered Swimming - Hand Force Pattern Analysis - Other Methods